Stroke care during the COVID-19 pandemic: Case numbers, treatments, and mortality in two large German stroke registries - Brunssen, Alicia; Rücker, Viktoria; Heuschmann, Peter; Held, Jana; Hermanek, Peter; Berlis, Ansgar; Hecht, Martin; Berger, Klaus (Frontiers in Neurology, 2022)
Background and purpose At the beginning of the SARS-CoV-2 pandemic, an alarming decline in hospitalizations for stroke was reported in several countries, including Germany. We assessed hospitalization numbers and indicators of the quality of stroke care in 2020 during the pandemic containment measures. Materials and methods The analysis was based on data of two large stroke quality assurance registries in the north and the south of Germany (Qualitätssicherung Schlaganfall Nordwestdeutschland and Bayerische Arbeitsgemeinschaft für Qualitätssicherung in der stationären Versorgung). We included 395 hospitals with 467,931 documented cases in 2018–2020. The time interval between admission and thrombolysis, frequency of systemic thrombolysis and intra-arterial therapy (IAT), National Institutes of Health Stroke Scale (NIHSS) score on admission and in-hospital mortality were assessed. Changes in the second (Q2) and fourth (Q4) quarters of 2020 were compared to corresponding quarters in 2019 by chi-squared tests. Results Hospitalization numbers decreased in the two stroke registries by 8% and 10% in Q2 of 2020 and by 5% and 15% in Q4 of 2020 compared to the same quarters in 2019, respectively. The decline was particularly seen in women and patients with transient ischemic attacks. In cases with cerebral infarction, no increase in NIHSS scores on admission was observed, and the proportion of patients with a time interval between admission and thrombolysis of ≤60 min was unchanged. No clear pattern was found in the frequency of systemic thrombolysis and IAT. In one of the registries, in-hospital mortality of patients with cerebral infarction increased in Q2 of 2020 compared to Q2 of 2019. Conclusion Case numbers slightly decreased under pandemic conditions, while our quarterly analysis indicated that the quality of stroke care was largely unchanged throughout the year 2020.